METHODS OF INSTALLATION OF WIRE ROPE AND BINDER WHEN SECURING LOADS - Bozorov R.Sh.; Boboev D.Sh. (PEDAGOGS, 2025)
Abstract: The article shows the suitability of fastening tools in the process of securing cargo in railway transport and the methods of their installation. Fastening tools for safe transportation of cargo are studied, measures and proposals for their selection are developed. In addition, the technical characteristics of the main models of fastening elements are analyzed, and proposals are made for the installation of tensioners and fasteners to eliminate the shortcomings of the existing system.